Penarapan E-Learning Berbantuan Canva Untuk Meningkatkan Hasil Belajar Siswa - Oky Dwi Noor Jannah; Wawan Shokib Rondli (ILUMINASI: Journal of Research in Education, 2023)
The purpose of this study was to determine the increase in learning outcomes and student learning activities in the application of e-learning to improve learning outcomes in students of class VI SD 2 Jepang. This research was contucted at SD 2 Jepang, Mejobo, Kudus in class VI with a total of 29 students. This study used classroom action research consisting of 2 cycles. Each cycle consists of 2 meetings. Data collection techniques used are test and observation sheets. Data analusis techniques using quantitative data analysis and qualitatitve data analysis. The result showed that the student learning outcomes in pre-cycle showed the number 70 then became 74 in cycle I and became 86 in cycle II. While student learning activities in the pre-cycle show a number of 70 rising to 73 in cycle I and to 74 in cycle II